SYSTEM OF FORMATION OF DEVELOPMENT OF FUTURE HEADS’ OF GENERAL EDUCATIONAL INSTITUTION READINESS FOR STRATEGIC MANAGEMENT IN MASTER’S DEGREE COURSES - Olha V. Lebid (Вісник Університету імені Альфреда Нобеля. Серія Педагогіка і психология)
The article scientifically substantiates the system of forming the readiness of the future head of a comprehensive educational institution for strategic management in the conditions of magistracy. The components of the system are defined: subject-object, conceptual, content, process-technological and control-productive ones. The essence of the subject-object component, which involves the identification of subjects (teachers and heads of institutions of general secondary education with whose help graduates fulfil their management practice) and objects (tertiary students at the second, master’s, level of studies in the educational-professional program “Management of an educational institution” – specialty 073 “Management”). The essence of the conceptual component is considered. It contains the goal (formation of the readiness of the future head of a comprehensive educational institution for strategic management in the conditions of the magistracy in accordance with the modern needs in their professional activities for the sake of which the structural and functional model is created), the tasks, the principles (systemic and systematic, the connection of learning with practical activity, consciousness and activity of learning, the reinforcement of knowledge), methodological principles (systemic, synergetic, competence-oriented, student-centered, active, axiological, acmeological, andragogical), and pedagogical conditions. The substantive component is substantiated, which is implemented through the introduction of the educationalprofessional program “Management of an educational institution” – the specialty 073 “Management”. The procedural-technological component of the system of forming the readiness of the future head of a comprehensive educational institution for strategic management in the conditions of the magistracy is revealed. It is based on the harmonious combination of dialogue-discussion, simulation and informationdistance learning technologies and is implemented through lectures, seminars and practical classes, independent work, consultations, trainings, practical training, research work. The essence of the controland-effect component, which provides for evaluation of readiness of the future head of a comprehensive educational institution for strategic management (criteria, indicators, levels of formation), is determined. A complex of monitoring, corrective and diagnostic procedures that are performed after the completion of each stage of the system and when finalizing it is suggested: inbound and outbound diagnostics; current, final, and reflexive control. The result is characterized by a positive dynamics of levels of readiness for strategic management.